The Impact of Angiotensin-Converting Enzyme Inhibitors or Angiotensin II Receptor Blockers on Clinical Outcomes of Acute Kidney Disease Patients: A Systematic Review and Meta-Analysis - Chen, Jui-Yi; Tsai, I-Jung; Pan, Heng-Chih; Liao, Hung-Wei; Neyra, Javier A.; Wu, Vin-Cent; Chueh, Jeff S. (Frontiers in Pharmacology, 2021)
Background Acute kidney injury (AKI) may increase the risks of chronic kidney disease (CKD), development of end-stage renal disease (ESRD), and mortality. However, the impact of exposure to angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers (ACEi/ARB) in patients experiencing AKI/ acute kidney disease (AKD) is still unclear. Methods In this systematic review, we searched all relevant studies from PubMed, Embase, Cochrane, Medline, Collaboration Central Register of Controlled Clinical Trials, Cochrane Systematic Reviews, and ClinicalTrials.gov until July 21, 2020. We evaluated whether the exposure to ACEi/ARB after AKI onset alters recovery paths of AKD and impacts risks of all-cause mortality, recurrent AKI or incident CKD. We rated the certainty of evidence according to Cochrane methods and the GRADE approach. Results A total of seven articles, involving 70,801 patients, were included in this meta‐analysis. The overall patient mortality rate in this meta-analysis was 34.2%. Among AKI patients, all-cause mortality was lower in ACEi/ARB users than in ACEi/ARB non-users (log Odds-Ratio (OR) -0.37, 95% confidence interval (CI): [−0.42 to −0.32], p < 0.01). The risk of recurrent adverse kidney events of after AKI was lower in ACEi/ARB users vs. non-users. (logOR, -0.25, 95% CI, [−0.33 to −0.18], p < 0.01). The risk of hyperkalemia was higher in ACEi/ARB users than in non-users (logOR 0.43, 95% CI: [0.27 to 0.59], p < 0.01). Patients with continued use of ACEi/ARB after AKI also had lower mortality risk than those prior ACEi/ARB users but who did not resume ACEi/ARB during AKD (logOR -0.36, 95% CI: [−0.4 to −0.31], p < 0.01). Conclusions The exposure to ACEi/ARB after AKI is associated with lower risks of all-cause mortality, recurrent AKI and progression to incident CKD. Patients with AKI may have a survival benefit by continued use of ACEi/ARB; however, higher incidence of hyperkalemia associated with ACEi/ARB usage among these patients deserves close clinical monitoring.